Aliyeva , Matanat - (:unkn) unknown (My University, 2026)
Matanat Latif Aliyeva entered the Faculty of Construction of the Azerbaijan Institute of Civil Engineers in 1984, specializing in Economics and Organization of Construction. She graduated in 1989 with the qualification of Engineer-Economist. In 1991, she began her academic career at the Azerbaijan Institute of Civil Engineers (now the Azerbaijan University of Architecture and Construction). Over the years, she has held the positions of laboratory assistant, assistant lecturer, lecturer at the Department of Construction Marketing and Management (since 2002), and senior lecturer at the Department of Service Sector Economics and Management (since 2011). She currently serves as a Senior Lecturer at the Department of Business Economics and Management of the Azerbaijan University of Architecture and Construction. Matanat Latif Aliyeva is the author of 48 scientific articles, 38 conference papers, 30 course curricula, one methodological manual, and two monographs. Her publication record also includes two articles indexed in Scopus and one article indexed in the Web of Science. Her research interests include digital economy, artificial intelligence, production infrastructure, management, green economy, space economy, and economic security.